2016
DOI: 10.18632/oncotarget.9275
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH blockade combined with radiation therapy and temozolomide prolongs survival of orthotopic glioblastoma

Abstract: Glioblastoma multiforme (GBM) is the most common malignant brain tumor in adults. The current standard of care includes surgery followed by radiotherapy (RT) and chemotherapy with temozolomide (TMZ). Treatment often fails due to the radiation resistance and intrinsic or acquired TMZ resistance of a small percentage of cells with stem cell-like behavior (CSC). The NOTCH signaling pathway is expressed and active in human glioblastoma and NOTCH inhibitors attenuate tumor growth in vivo in xenograft models. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 49 publications
8
59
0
Order By: Relevance
“…In our study, PyClone analysis suggested that cells harboring NOTCH1 mutations were sensitive to radiation, whereas those harboring EGFR and MGA mutations were resistant to radiation. Recent studies suggest that activation of the NOTCH signaling pathway is related to radiation resistance in tumor cells (19)(20)(21). OncodriveROLE, a machine learning-based approach, indicated that the NOTCH1 p.Cys1374Tyr mutation, as detected in our study, is a "loss-of-function" mutation (22,23).…”
Section: Discussionsupporting
confidence: 63%
“…In our study, PyClone analysis suggested that cells harboring NOTCH1 mutations were sensitive to radiation, whereas those harboring EGFR and MGA mutations were resistant to radiation. Recent studies suggest that activation of the NOTCH signaling pathway is related to radiation resistance in tumor cells (19)(20)(21). OncodriveROLE, a machine learning-based approach, indicated that the NOTCH1 p.Cys1374Tyr mutation, as detected in our study, is a "loss-of-function" mutation (22,23).…”
Section: Discussionsupporting
confidence: 63%
“…Yet in the context of drug treatment, this promotion of a slow-cycling state may have the untoward consequence of conferring resistance. The Notch-dependency of the refractory GSC state may thus portend opportunities for combination therapy, some of which are now being explored in pre-clinical and early clinical studies (Cenciarelli et al, 2014; Xu et al, 2016; Yahyanejad et al, 2016) .…”
Section: Discussionmentioning
confidence: 99%
“…Notch-1 and its ligands are overexpressed in many GBM cell lines and primary tumors and activation of this pathway contributes to CSC survival and proliferation (Purow et al, 2005; Kanamori et al, 2007). A recent study confirmed that Notch blockade combined with a standard-of-care treatment has an anti-CSC effect and provides an improved survival benefit for GBM patients as well as new insights for further clinical studies (Yahyanejad et al, 2016). …”
Section: Gscs and Their Characteristicsmentioning
confidence: 91%